Post COVID-19 irritable bowel syndrome - Marasco, Giovanni; Cremon, Cesare; Barbaro, Maria Raffaella; Cacciari, Giulia; Falangone, Francesca; Kagramanova, Anna; Bordin, Dmitry; Drug, Vasile; Miftode, Egidia; Fusaroli, Pietro; Mohamed, Salem Youssef; Ricci, Chiara; et al. (My University, 2022)
The long-term consequences of COVID-19 infection on the gastrointestinal tract remain unclear. Here, we aimed to evaluate the prevalence of gastrointestinal symptoms and post-COVID-19 disorders of gut-brain interaction after hospitalisation for SARS-CoV-2 infection.
Keywords: COVID-19; irritable bowel syndrome